2007
DOI: 10.17159/2078-516x/2007/v19i3a260
|View full text |Cite
|
Sign up to set email alerts
|

Changes in neutrophil count, creatine kinases and muscle soreness after repeated bouts of downhill running

Abstract: Objective. A primary objective was to examine circulating neutrophil count after repeated bouts of downhill running. An additional aim was to determine creatine kinase (CK) levels during the initial 12 hours, after repeated DHRs.Design. Eleven healthy, untrained Caucasian males performed 2 x 60 min bouts of DHR (-13.5%), spaced 14 days apart, at a speed equal to 75% VO 2max on a level grade. Blood was collected before, after, and every hour for 12 hours, and every 24 hours for 6 days. Absolute neutrophil count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“… 21 , 23 , 25 , 30 , 40 , 41 Peak soreness can occur between 24 and 96 hours after the eccentric con tractions. 14 , 21 , 27 , 36 , 37 , 42 , 43 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 21 , 23 , 25 , 30 , 40 , 41 Peak soreness can occur between 24 and 96 hours after the eccentric con tractions. 14 , 21 , 27 , 36 , 37 , 42 , 43 …”
Section: Discussionmentioning
confidence: 99%
“…In these studies, the range has varied from pretest values of 83 units/L to 154 units/L; after 24 hours from 230 to 822 units/L; after 48 hours from 20 to 598 units/L; after 72 hours from 200 to 1,620 units/L; and after 96 hours from 132 to 500 units/L. 15 , 21 , 23 , 25 , 42 , 44 Two studies recorded peak CK levels of over 10,000 units/L. 16 , 39 In one training session in 1980, completed by Athletics West world-class runners who were asked to do 100 sit-ups with a 11.3 kg (25 pounds) weight on their chests, CK levels were recorded near 30,000 units/L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study formed part of a published study that reported on the responses of indirect markers of muscle damage to two bouts of downhill running [ 30 ]. Serum creatine kinase and delayed onset muscle soreness were significantly reduced after the second bout of running, thus demonstrating a repeated bout effect [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…At the start of the run, participants warmed up for 5 minutes by running on a level grade at the pre-determined speed. The treadmill was then lowered to a -13.5% decline and participants ran for 60 minutes [ 30 ]. The participants remained in the exercise testing laboratory (ETL) for 12 h after the run.…”
Section: Methodsmentioning
confidence: 99%